Pembuatan Aplikasi Bergerak Temu Ulang File Elektronik Berbahasa Indonesia dengan Memanfaatkan Java CLDC - Andre Kurniawan; Hapnes Toba (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
Smart Download is a mobile application that dedicated to search electronic documents in Indonesian(Bahasa Indonesia) throguh the Web. This application use the Advanced URL Google (spyder) to retrieve thedocuments from the Internet, that further will be enchanced with Porter Stemmer and the combination ofTF/IDF and vector space algorithm. The documents that need to be downloaded can be breakdown in partialparts. The implementation of the application used J2ME CLDC. The application is evaluated in a classroomsituation, the result shows that search is improved after the enhancement process.Keywords: Smart Download, Spyder Google, Porter Stemmer, Vector Space Algorithm.